2021
DOI: 10.35315/dakp.v10i1.8441
|View full text |Cite
|
Sign up to set email alerts
|

Etika Dan Kepatuhan Pajak

Abstract: National income is from tax revenue. Every year the tax revenue target always increases, but since 2008, the target revenue has never been able to. In addition, the tax compliance of the taxpayers in the DJP performance report shows a low percentage, even though taxpayers are expected to increase state revenue. There are many taxpayers who tax taxes illegally. So the question arises about how taxpayers' ethics taxation. This article is a conceptual article that is conducted based on the author's ideas and opin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
1
0
2
Order By: Relevance
“…The greater the demand for shares, the higher the share prices in the capital market, indicating that the company has a greater perceived value. Research by Hirdinis [51] found that firm size has a significant effect on firm value, consistent with the results of Sofyaningsih and Hardiningsih [52] and Nurhayati [53]. Larger companies are perceived to be better able to manage their business and return funds to their investors, which contributes to an increase in the value of the company.…”
Section: Firm Size On Firm Valuesupporting
confidence: 75%
“…The greater the demand for shares, the higher the share prices in the capital market, indicating that the company has a greater perceived value. Research by Hirdinis [51] found that firm size has a significant effect on firm value, consistent with the results of Sofyaningsih and Hardiningsih [52] and Nurhayati [53]. Larger companies are perceived to be better able to manage their business and return funds to their investors, which contributes to an increase in the value of the company.…”
Section: Firm Size On Firm Valuesupporting
confidence: 75%
“…When associated with the concept of taxation, control can be caused by the positive and negative impacts of taxation displayed in the media (Kunarti, 2019). There are three types of behavior in this theory according to Ajzen (1991) as cited in Hasanah & Ardini (2021), namely Behavioral Belief, Normative Belief, and Control Belief.…”
Section: Literature Review Theory Of Planned Behaviormentioning
confidence: 99%
“…Pajak adalah pembayaran wajib kepada pemerintah yang wajib dilakukan oleh orang pribadi atau badan, tanpa menerima imbalan langsung. Hal ini dimanfaatkan oleh negara untuk memenuhi kebutuhannya dan meningkatkan kesejahteraan atau kemakmuran penduduk (Hasanah & Ardini, 2021).…”
Section: Abstrakunclassified